District Level Hospital Diabetic Patients Referred to Intermediate Care: A Descriptive Analysis - Jansen, Rosa (Department of Public Health and Family Medicine, 2024)
Background Diabetes mellitus contributes considerably to morbidity and mortality. By analysing a South African cohort with diabetes-related adverse outcomes, the researchers felt that reviewing their past primary care may reveal contributing factors resulting in these outcomes. Methods A retrospective cohort design was used. Data from an existing district-level hospital database of referrals to intermediate care were analysed, focusing on diabetic adult patients referred between 1 November 2020 and 31 August 2021. Additional data were collected on the standard of primary care, investigations performed on admission and patient demise within 12 months of the research window. Results The cohort comprised 188 patients. The mean age was 64.4 years, 113 (60.1%) were female, and 98.1% had low socioeconomic status. The majority were admitted with strokes 130 (69.2%) and 139 (73.9%) were referred for intense short-term rehabilitation. A quarter of patients were newly diagnosed diabetics at admission. Of known diabetics, 44 (30.8%) had no HbA1c in the preceding two years. ACE-inhibitors were not prescribed adequately, and insulin initiation was delayed. Accessible data 12 months post review window revealed that 53 (28.2%) had demised and of those, 29 (54.7%) had demised within a month of initial admission. Conclusion Diabetic screening and management in primary care need improvement. It appears that guidelines were not followed adequately and potentially may have contributed to the outcomes experienced by this cohort, as well as subsequent costs to the health system. Contribution The authors recommend that barriers to following primary care diabetes guidelines be explored further in future research.